2014
DOI: 10.2174/1573403x10666140704111537
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and Noninvasive Assessment of Exercise-induced Ischemic Diastolic Response Using Pressure Transducers

Abstract: Left ventricular (LV) pressure curve shows early high-magnitude changes in the presence of induced ischemia. A dramatic rise in LV and left atrial end-diastolic pressures occurs within seconds to minutes in the presence of ischemia induced by dynamic or handgrip exercise as well as pacing of 38 to 183% and during short coronary balloon occlusion of 32 to 208% of baseline. Changes in relaxation or volumetric filling rate or ejection fraction were significantly less pronounced. Similar end-diastolic abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(108 reference statements)
1
3
0
Order By: Relevance
“…It is widely believed that diastolic dysfunction occurs independently or preceding a systolic dysfunction (Cazzaniga et al, 2007 ; Fontes-Carvalho et al, 2015 ; Manolas, 2015 ), we herein, found that the Nrf2 −/− mice with systolic dysfunction exhibited a higher degree of diastolic dysfunction after CEE in relation to WT mice. Previously, a co-occurrence of systolic and diastolic dysfunction has been noted in pathophysiological process of heart failure (Zile and Brutsaert, 2002 ; Patten and Hall-Porter, 2009 ; Maharaj, 2012 ) supporting that the loss of Nrf2 could be associated with both systolic and diastolic dysfunction and accelerate heart failure.…”
Section: Discussionsupporting
confidence: 62%
“…It is widely believed that diastolic dysfunction occurs independently or preceding a systolic dysfunction (Cazzaniga et al, 2007 ; Fontes-Carvalho et al, 2015 ; Manolas, 2015 ), we herein, found that the Nrf2 −/− mice with systolic dysfunction exhibited a higher degree of diastolic dysfunction after CEE in relation to WT mice. Previously, a co-occurrence of systolic and diastolic dysfunction has been noted in pathophysiological process of heart failure (Zile and Brutsaert, 2002 ; Patten and Hall-Porter, 2009 ; Maharaj, 2012 ) supporting that the loss of Nrf2 could be associated with both systolic and diastolic dysfunction and accelerate heart failure.…”
Section: Discussionsupporting
confidence: 62%
“…The results illustrated in Figure 3(a) show that such decrease in TCV would cause an increase of IVCD from 60 to 71 ms and a slight reduction of ðdP V /dtÞ max from 1780 to 1750 mmHg/s. For comparison, Figure 3(a) includes also two clinically measured normal pressure traces (digitized from literature [18,19]) which demonstrate a good agreement between our FE model and clinical observations. Besides the changes in values of the parameters derived from the pressure traces, an increased wall stress was detected in the endocardial and midmyocardial layers of the LV at the end of IVC (Figure 3(b)).…”
Section: Impact Of Decreased Transmural Conduction Velocity On the Fumentioning
confidence: 63%
“…dt) max = 1780 mmHg/s IVC time = 60 ms (dP/dt) max = 1750 mmHg/s IVC time = 71 ms (a) Effect of a 50% decrease of TCV on pressure rise in the LV during IVC. Pressure development obtained in the control simulation is compared with two normal pressure traces (in grey) digitized from literature[18,19]. (b) Effect of a 50% decrease of TCV on distribution of stresses (in the direction of myofibres) across the LV wall (from endocardium-0% to epicardium-100%) in the end of IVC.…”
mentioning
confidence: 99%
“… Time course of intraventricular pressure rise during IVC and the underlying increase of tension in LV wall under control conditions. (a) Simulated rise of intraventricular pressure and its comparison with digitalized experimental records published by Curtiss et al [ 14 ], Manolas [ 15 ], and Kern et al [ 16 ]. Note that the duration of IVK (∼60 ms) and dp / dt max⁡ (1780 mm Hg/s) agrees with clinically measured values (61 ms, 63 ms, 61 ms, and 1790 mm Hg/s, 1730 mm Hg/s, and 2130 mm Hg/s, resp.).…”
Section: Figurementioning
confidence: 99%